Pelaksanaan sistem kerajaan eletronik dan impaknya terhadap organisasi dan masyarakat setempat: Kajian kes Majlis Bandaraya Alor Setar - Mohamad Farid, Yusoff (2015)
This research aimed to study on the implementation of electronic government system in selected local authorities, Alor Setar City Council (MBAS) and its impacts on the organization and the local community. Electronic government was introduced on 1999 through Multimedia Super Corridor (MSC) which was one of the plans under Vision 2020. In Malaysia, the main aim on introducing electronic government was to make it acts as a medium to transform government sector and also as the trigger of MSC development success. Electronic government system is also a transformation in enhancing service quality by local authorities towards local community. Therefore, government has taken several proactive initiatives in enhancing the electronic based administration and management of country, starting from the local authority level. Besides that, people had been exposed with consumers towards information and communication technology (ICT) which made the implementation of electronic government system, as people demands a service that is effective, efficient, practical, and fast in line with progress of the nation. The implementation of electronic government especially in local authorities has not only changed the way of service providing, it also changes the communication structure of the authorities with local people. The people get benefits in connecting with local authorities’ service and getting information by using the application provided by the local authorities. However, this study found that there are still some constraints that dampen the process in implementing electronic government fully in the local authority level because of lacks of innovation in providing services.